Emotion regulation difficulties and social control correlates of smoking among pregnant women trying to quit. (February 2019) - Fillo, Jennifer; Kamper-DeMarco, Kimberly E.; Brown, Whitney C.; Stasiewicz, Paul R.; Bradizza, Clara M.
Abstract: Approximately 15% of US women currently smoke during pregnancy. An important step toward providing effective smoking cessation interventions during pregnancy is to identify individuals who are more likely to encounter difficulty quitting. Pregnant smokers frequently report smoking in response to intrapersonal factors (e.g., negative emotions), but successful cessation attempts can also be influenced by interpersonal factors (i.e., influence from close others). This study examined the association between emotion regulation difficulties, positive and negative social control (e.g., encouragement, criticism), and smoking cessation-related variables (i.e., smoking quantity, withdrawal symptoms) among pregnant smokers. Data were drawn from the pretreatment wave of a smoking cessation trial enrolling low-income pregnant women who self-reported smoking in response to negative affect ( N = 73). Greater emotion regulation difficulties were related to greater smoking urges (b = 0.295, p = .042) and withdrawal symptoms (b = 0.085, p = .003). Additionally, more negative social control from close others was related to fewer smoking days (b = −0.614, p = .042) and higher smoking abstinence self-efficacy (b = 0.017, p = .002). More positive social control from close others interacted with negative affect smoking (b = −0.052, p = .043); the association between negative affect smoking and nicotine dependence (b = 0.812, p < .001) only occurred at low levels of positive social control. Findings suggest that emotion regulation difficulties may contribute to smoking during pregnancy by exacerbating women's negative experiences related to smoking cessation attempts. Negative social control was related to lower smoking frequency and greater confidence in quitting smoking, suggesting that it may assist pregnant smokers' cessation efforts. Positive social control buffered women from the effects of negative affect smoking on nicotine dependence. Trial registration: ClinicalTrials.gov, NCT01163864 Highlights: Cessation correlates are examined in low-income pregnant smokers trying to quit Emotion regulation difficulties predict greater smoking urges, withdrawal symptoms Negative social control predicts fewer smoking days, greater abstinence self-efficacy Positive social control buffered effects of negative affect smoking on dependence